Addressing the Threat of Childhood Obesity: Preventive Strategies at the DENKESYAH Madiun Polyclinic - Ibnu Sina, Ibnu Sina; Agusta Dian Ellina (Universitas STRADA Indonesia, 2025)
Obesity represents a significant public health challenge, particularly in Indonesia. The World Health Organization reported that around 39 million children under the age of five were overweight or obese in 2020. In Indonesia, approximately 13.5% of adults aged 18 years and older are overweight, with 28.7% and 15.4% classified as obese at BMI thresholds of ≥25 and ≥27, respectively. In East Java, the prevalence of obesity among children under five increased from 5.67% in 2020 to 8% in 2021. To address this issue, a community engagement initiative was conducted at the DENKESYAH Madiun Polyclinic, East Java, which included health counseling, group exercise, distribution of an obesity prevention pocket book, and educational seminars involving internal medicine and pediatric specialists. The intervention aimed to raise parental and community awareness regarding the risks of childhood obesity and promote healthy lifestyle practices. Statistical analysis using SPSS revealed a significant difference between pretest and posttest scores (Z = -5.361, p = 0.000), confirming the effectiveness of the intervention in improving participants’ understanding of obesity. These findings emphasize the importance of community-based interventions in combating childhood obesity and promoting healthier lifestyles among children, and they may serve as a reference model for preventive healthcare programs in similar settings